Patient-reported disability in the general Japanese population was associated with medical care visits for low back pain, regardless of pain intensity - Ono, Rei; Yamazaki, Shin; Takegami, Misa; Suzukamo, Yoshimi; Konno, Shinichi; Kikuchi, Shinichi; Fukuhara, Shunichi (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2015)
Race/ethnicity is known to affect pain severity and the emotional aspects of pain, with medical care visits also reported to differ according to race/ethnicity. It has been hypothesized that there is an interactive relationship between pain intensity and patient-reported disability and that the interactive relationships are related to medical care visits. However, it remains unclear whether the association between patient-reported disability and medical care visits for low back pain (LBP) are dependent on the pain intensity. The aims of this study were to examine the prevalence of medical care visits among members of the Japanese general population and to analyze the association between patient-reported disability and medical care visits for LBP patients, regardless of the pain intensity. From a random sample of the general Japanese population (n = 2962), we focused on those who experienced LBP within the past month. Subjects were asked about the number of medical care visits (medical clinic or complementary/alternative medical clinic) for LBP. Patient- reported disability was assessed using the Roland-Morris disability questionnaire (RDQ). Pain intensity of LBP was assessed by visual analog scale. To examine the association between RDQ and medical care visits among people with LBP, we used multiple logistic regression analysis and the trend analysis for the RDQ. Of 841 reporting LBP in the past month, 285 (33.9 %) visited a medical care facility. After adjusting for pain intensity and other confounding factors, the odds ratios for the RDQ categories 1-5, 6-10, 11-15, and >16 were compared with the RDQ categories 0, 1.13 (95 % CI 0.731.73), 2.05 (95 % CI 1.17-3.60), 2.21 (95 % CI 1.06-4.62), and 4.0 (95 % CI 1.60-9.98), respectively (p for trend <0.01). Patient-reported disability was associated with medical care visits for LBP, regardless of the pain intensity, with the results similar to those obtained for other races/ethnicities.